(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
Crude oil was extracted from Adenopus breviflorusbenthseeds using n-hexane and the extracted oil was degummed, neutralized and bleached. Oil sample at each stage was assessed for physicochemical parameters and fatty acid composition. The oil yield was 54.35± 0.120%. The specific gravity (at 25oC) of the oil was 0.901±0.001 and the refractive index (at 25oC) was 1.472±0.012. Processing of the crude oil resulted in progressive decrease in turbidity, colour, free fatty acid, acid value, peroxide value and saponification value. There was increase in smoke point (202.00±0.10 to 239.00±0.30oC), flash point (305.00±0.78 to 322.00±1.05oC) and fire point (352.00±1.00 to 359.00±1.25oC) as well as iodine value (112.50 to 120.20) and total fatty acid during the processing of the oil. The fatty acids detected in the oil samples were lauric myristic, palmitic, stearic, oleic, linoleic and linolenic acids. The predominant fatty acid was linoleic acid (57.597 ?59.774%) followed by oleic acid (11.099 ? 12.766%) while the least fatty acid was lauric acid (0.053 ?0.355%). Bangladesh J. Sci. Ind. Res.51(3), 159-166, 2016